The study of the functionality of cardiomyocytes obtained from induced pluripotent stem cells for the modeling of cardiac arrhythmias based on long QT syndrome - M. M. Slotvitsky; V. A. Tsvelaya; S. R. Frolova; E. V. Dement’eva; K. I. Agladze (Вавиловский журнал генетики и селекции)
There are risk factors that lead the normal conduction of excitation in the heart into a chaotic one. These factors include hereditary and acquired channelopathies. Many dangerous changes in the work of the heart can be identified using the patient’s electrocardiogram. Such relatively easily detectable changes include the long QT interval syndrome (LQTS). Despite a relatively high prevalence of hereditary LQTS, to which it is necessary to add both hereditary and induced LQTS as well as the ease of detection on the ECG, the mechanism of reentry formation in this syndrome is still unknown. What should be noted is a high variability of the hereditary syndrome and the fact of the connection between the increase in the heart rate and the risk of cardiac arrest. After an electrophysiological study on individual cardiac cells from patients with the LQT syndrome, it became apparent that the search for a mechanism for the transition of the normal heart rhythm to chaotic and fibrillation cannot be limited to recording ion currents in single cells. To solve this problem, we need a model of the behavior of cardiac tissue which reflects the relationship of various factors and the risk of reentry. In order to create an experimental model of LQTS in our work, the iPSC of a patient-specific line from a healthy patient was differentiated into a monolayer of cardiac cells and the parameters of the excitation propagation were studied depending on the stage of differentiation. It was shown that a stable value of the propagation velocity and the response to periodic stimulation in the range of physiological values, are reached after the 30th day of differentiation.